2018
DOI: 10.12955/cbup.v6.1278
|View full text |Cite
|
Sign up to set email alerts
|

ASSOCIATION OF THE ADRB2 GENE POLYMORPHIC VARIANT C79G (rs1072714) WITH THE COURSE OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN OBESE AND NON-OBESE PATIENTS

Abstract: Introduction: Attention has been paid to studying the role of the sympathetic nervous system and polymorphism of the β2-adrenoceptor genes in the development of chronic obstructive pulmonary disease (COPD) in recent years, but the findings of the studies contradict each other.Objective:  To establish an association between the ADRB2 gene polymorphic variant C79G (rs1072714) in obese and non-obese COPD patients.Methods: The study involved 48 obese COPD patients and 52 nonobese COPD patients. The ADRB2 gene poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…За даними різних досліджень, у патогенезі ХОЗЛ важливу роль відіграють різноманітні гени, які мають вплив на процеси запалення, фіброзу та ре-гуляції реактивності бронхів [10,11]. Зокрема із розвитком [13], тяжкістю перебігу ХОЗЛ [6] та відповіддю до бета-2 агоністів асоціюється поліморфізм гена ADRB2 [12].…”
Section: вступunclassified
“…За даними різних досліджень, у патогенезі ХОЗЛ важливу роль відіграють різноманітні гени, які мають вплив на процеси запалення, фіброзу та ре-гуляції реактивності бронхів [10,11]. Зокрема із розвитком [13], тяжкістю перебігу ХОЗЛ [6] та відповіддю до бета-2 агоністів асоціюється поліморфізм гена ADRB2 [12].…”
Section: вступunclassified
“…But multiple studies indicate an important role of different genes in the regulation of inflammation, fibrosis and airways responsiveness [11]. One of such genes, that was shown to be related to the COPD development [12] and severity [13], and also response to beta-2 agonists, is beta-2 adrenergic receptor (ADRB2) gene [14].…”
Section: Introductionmentioning
confidence: 99%
“…As has been stated in guidelines, COPD development requires a combination of environmental and internal factors, and multiple studies have suggested an important role for several genes related to the regulation of inflammation, fibrosis, and airway responsiveness 11 . One of these is adrenoreceptor beta 2 (ADRB2), which some studies have shown to be related to COPD development 12 , severity 13 , and response to beta-2 agonists 14 . One study showed varying prevalence of ADRB2 gene alleles in COPD patients and healthy controls 15 and there is also data suggesting that ADRB2 polymorphisms are related to the response to inhaled corticosteroids 16, 17 .…”
Section: Introductionmentioning
confidence: 99%